Cultural Diversity And Its Impact On The Development Of Aculture Of Sharing And Community Peace From The View Of Social Work - Nizar Abdel-Sada Al-Nasser, Asst. Prof. Dr (lark, 2023)
The research tagged with cultural diversity in Iraq and its impact on the development of a culture of human rights aims to shed light on the importance of cultural diversity in our world today, considering that cultural diversity represents a common characteristic of human heritage in general, and knowledge of the culture of the local community in particular on the other hand, as well as knowledge The importance of the culture and development of human rights within society and its various institutions, as well as the protection of these rights guaranteed by the constitution and the law for all members of society regardless of their sects, religions and ethnicities, because they constitute the diverse social fabric of the country and through long historical periods, where it was known about Iraq as the home of coexistence since ancient times. The different peoples and groups lived in it with great peace and love. The study also touched on some of the obstacles that prevent the achievement of cultural diversity or negatively affect the continuation of social coexistence as a result of some events and variables and as a result of external or internal factors that are alien to the norms and values of people that characterized Iraqi society in the past and present